1999
DOI: 10.1080/026567399285828
|View full text |Cite
|
Sign up to set email alerts
|

Thermal radiosensitization and repair inhibition in human melanoma cells: a comparison of survival and DNA double strand breaks

Abstract: Human melanoma cells (SK-mel-3) were treated with combinations of radiation and hyperthermia treatment and survival (using the colony forming assay) and DNA double strand breaks (dsb's) (using pulsed field gel electrophoresis) were measured for immediate and delayed plating. The cells were treated in plateau phase, so that delayed plating would result in repair of potentially lethal damage (PLD). Delayed plating showed PLDR for both the survival and the dsb end-point. One hour of heating after irradiation show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 34 publications
0
8
0
2
Order By: Relevance
“…So far, many studies have investigated the effect of high temperature, given prior to or following the mutagenic treatment, on the repair efficiency and/or on resistance to the mutagen (Raaphorst et al, 1999;Schmidt-Rose et al, 1999;Kaszenman et al, 2000;El-Awady et al, 2001). However, very few attempts have been made to evaluate the effect of resistance to stress on the repair efficiency.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…So far, many studies have investigated the effect of high temperature, given prior to or following the mutagenic treatment, on the repair efficiency and/or on resistance to the mutagen (Raaphorst et al, 1999;Schmidt-Rose et al, 1999;Kaszenman et al, 2000;El-Awady et al, 2001). However, very few attempts have been made to evaluate the effect of resistance to stress on the repair efficiency.…”
Section: Discussionmentioning
confidence: 98%
“…A few studies concerning the effect of environmental conditions on DNA repair efficiency were also conducted although the results seem to be controversial. Thus, while Raaphorst, Ng and Yang (1999), Schmidt-Rose et al (1999), and El-Awady, Dikomey and Dahm-Daphi (2001) found high temperature as repair-inhibiting factor, Kaszenman, Candreva and Nunes (2000) reported about improved DNA repair efficiency at high temperature. The response to stressful conditions and mutagenic treatment may be modulated by stress resistance of the genotype.…”
Section: Introductionmentioning
confidence: 91%
“…In addition to complementary biologic effects with radiation and chemotherapy, mechanisms for direct effect include protein denaturization including inhibition of sub-lethal and potentially lethal damage repair through inactivation of DNA repair pathways leading to mitotic catastrophe, induction of senescence, apoptosis, and necrosis. (21)(22)(23)(24)(25)(26)(27)(28) Research has revealed that protein denaturization is a key biologic effect of hyperthermia at modest temperature elevations. (29) The activation energeries for protein denaturization and heat induced cell death were noted to be within the same range.…”
Section: Mechanism Of Cell Death With Hyperthermiamentioning
confidence: 99%
“…Son utilisation pendant la radiothérapie pourrait théoriquement augmenter la réponse de la tumeur à l'irradiation par différents mécanismes : coopération cytocinétique, ciblage de l'hypoxie, inhibition des mécanismes de réparation de l'ADN, ou élévation du flux sanguin diminuant ainsi l'hypoxie [100][101][102][103][104][105][106][107][108]. Deux essais cliniques ont montré une amélioration du taux de contrôle tumoral lors de l'utilisation conjointe de la radiothérapie et de l'hyperthermie dans les cancers des voies aérodigestives supérieures [109,110].…”
Section: Hyperthermieunclassified